The cell type-specific effect of TAp73 isoforms on the cell cycle and apoptosis - Holčáková, Jitka; Češková, Pavla; Hrstka, Roman; Müller, Petr; Zdražilová Dubská, Lenka; Coates, Philip J; Paleček, Emil; Vojtěšek, Bořivoj (Cellular and Molecular Biology Letters, 2008)
p73, a member of the p53 family, exhibits activities similar to those of p53, including the ability to induce growth arrest and apoptosis. p73 influences chemotherapeutic responses in human cancer patients, in association with p53. Alternative splicing of the TP73 gene produces many p73 C- and N-terminal isoforms, which vary in their transcriptional activity towards p53-responsive promoters. In this paper, we show that the C-terminal spliced isoforms of the p73 protein differ in their DNA-binding capacity, but this is not an accurate predictor of transcriptional activity. In different p53-null cell lines, p73beta induces either mitochondrial-associated or death receptor-mediated apoptosis, and these differences are reflected in different gene expression profiles. In addition, p73 induces cell cycle arrest and p21(WAF1) expression in H1299 cells, but not in Saos-2. This data shows that TAp73 isoforms act differently depending on the tumour cell background, and have important implications for p73-mediated therapeutic responses in individual human cancer patients.
Keywords: nádorový supresorový protein p53; Protein Isoforms; financování organizované; Cell Cycle; Cell Line; jaderné proteiny; signální transdukce; DNA-Binding Proteins; Transcriptional Activation; trans-aktivátory; Gene Expression Profiling; apoptóza; Protein Binding; Nuclear Proteins; alternativní sestřih; Signal Transduction; Tumor Suppressor Protein p53; Trans-Activators; Transcription, Genetic; genetická transkripce; buněčný cyklus; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Financing, Organized; nádorové supresorové proteiny; zvířata; protein - isoformy; Alternative Splicing; Humans; aktivace transkripce; vazba proteinů; Tumor Suppressor Proteins; DNA vazebné proteiny; stanovení celkové genové exprese; buněčné linie; Oligonucleotide Array Sequence Analysis; lidé; Apoptosis; Animals